KINERJA PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK (P2TP2A) DALAM PENANGANAN TINDAK KEKERASAN ANAK DI KABUPATEN BENGKALIS - Puteri, Jesika; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Actions of child abuse’s have increased every year in Bengkalis Regency. Therefore, the Government of Bengkalis Regency established an integrated Community-based Empowerment Center for Women and Children (P2TP2A) with the aim of providing fast, appropriate and integrated physical and non-physical services in order to provide protection for women and children who are vulnerable to violence . This study aims to get an idea of how P2TP2A performs and identify the factors that influence the performance of P2TP2A in handling child abuse in Bengkalis Regency. The theoretical concept used is the performance theory of Dwiyanto with indicators of productivity, service quality, responsiveness, responsibility, and accountability. This study uses a qualitative method that is descriptive, the selection of informants using the Purposive sampling technique. The technique of collecting data through interviews, observation, and documentation. The results of this study indicate that the performance of Bengkalis P2TP2A has not been effective. Some influencing factors include budget, socialization, and communication. This method uses performance theory from Dwiyanto with indicators of productivity, service quality, responsiveness, responsibility, and accountability. from the results of this study it was found that the performance of P2TP2A had not been effective because there were several factors that inhibited namely in the form of budget, socialization, and communication. It is better for P2TP2A to further improve the performance of Bengkalis P2TP2A Regency management starting from productivity, service quality, responsiveness, responsibility, and accountability, and need to prepare permanent staff who can stand by at any time providing services according to procedures.Keywords : Performance, P2TP2A, Child Abuse